2021
DOI: 10.21203/rs.3.rs-218699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Improve Testicular Steroidogenesis Machinery Dysfunction In Benzo [α] Pyrene Challenged Rats

Abstract: Although Zinc oxide nanoparticles (ZnO NPs) in low doses have potentially positive effects on reproduction by their antioxidant effects, the defensive role of Zinc nanomaterials against environmental pollutants that affect male reproduction has not been adequately studied. We designed our study to assess the impact of ZnO NPs towards reproductive dysfunction induced by Benzo[α]Pyrene (B[a]P). Forty-eight mature male rats were randomly distributed into six equal groups: G1; negative control, G2&3- positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…These results suggest that the genotoxic effects of ZnO NPs on germ cells can be observed by increasing the expression of the DNA damage response marker γ-H2AX. Daoud et al showed that ZnO NPs, at their investigated doses and given their properties (10 mg/kg/BW), exerted an ameliorative effect against benzo[α]pyrene by decreasing oxidative stress and by increasing the expression levels of steroidogenic enzymes, resulting in the repair of tissue abnormalities (46). And Anan et al showed that ZnO NPs effectively ameliorate the deleterious histological and biochemical changes induced by cyclophosphamide in rat testis through their antioxidant and anti-apoptotic effects (47).…”
mentioning
confidence: 99%
“…These results suggest that the genotoxic effects of ZnO NPs on germ cells can be observed by increasing the expression of the DNA damage response marker γ-H2AX. Daoud et al showed that ZnO NPs, at their investigated doses and given their properties (10 mg/kg/BW), exerted an ameliorative effect against benzo[α]pyrene by decreasing oxidative stress and by increasing the expression levels of steroidogenic enzymes, resulting in the repair of tissue abnormalities (46). And Anan et al showed that ZnO NPs effectively ameliorate the deleterious histological and biochemical changes induced by cyclophosphamide in rat testis through their antioxidant and anti-apoptotic effects (47).…”
mentioning
confidence: 99%